2009
DOI: 10.1152/japplphysiol.91264.2008
|View full text |Cite
|
Sign up to set email alerts
|

Protein and carbohydrate supplementation after exercise increases plasma volume and albumin content in older and young men

Abstract: This study examined whether increased plasma volume (PV) and albumin content (Alb(cont)) in plasma for 23 h after exercise were attenuated in older subjects compared with in young adult subjects, and if this attenuation abated by supplementation with protein and carbohydrate (CHO) immediately after exercise. Eight moderately active older (approximately 68 yr) and 8 young (approximately 21 yr) men performed two trials: control (CNT) and Pro-CHO in which subjects consumed placebo (0.5 kcal, 0 g protein, 0.5 mg N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 40 publications
3
34
2
Order By: Relevance
“…Carbohydrate-protein feeding (0.55 g·kg -1 carbohydrate, 0.18 g·kg -1 protein) immediately after a bout of high intensity exercise has been shown to influence plasma albumin content and plasma volume over a 23 h recovery period (Okazaki et al 2009). Similarly, in the present study plasma albumin content was increased from 1 h after drinking during WP, a difference that was not evident during W and this change in plasma albumin content likely explains why plasma volume was greater at 3 h and 4 h during WP compared to W.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbohydrate-protein feeding (0.55 g·kg -1 carbohydrate, 0.18 g·kg -1 protein) immediately after a bout of high intensity exercise has been shown to influence plasma albumin content and plasma volume over a 23 h recovery period (Okazaki et al 2009). Similarly, in the present study plasma albumin content was increased from 1 h after drinking during WP, a difference that was not evident during W and this change in plasma albumin content likely explains why plasma volume was greater at 3 h and 4 h during WP compared to W.…”
Section: Discussionmentioning
confidence: 99%
“…The ingestion of protein post-exercise has been shown to increase plasma albumin content (Okazaki et al 2009), which as the main plasma protein is the primary contributor to oncotic pressure and may play a role in post-exercise fluid balance, although this has not yet been examined in a post-exercise rehydration context.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, one study showed that when young and elderly individuals ingested placebo (i.e., non-energy ingestion) just after acute high-intensity interval exercise, the ability of recovery of Alb cont and PV after exercise was generally blunted in elderly individuals compered to young individuals. In contrast, Alb cont and PV recovered more when they consumed a protein and CHO mixture compared to consumed placebo in both individuals [35].…”
Section: Effects Of Exercise Training On Thermoregulation In the Eldementioning
confidence: 89%
“…An increase in plasma protein (mainly albumin content) also contributes by drawing fluids into the intravascular space from the interstitium [33][34][35]. Facilitated Na + and water reabsorption [33,36] and an enhancement of voluntary fluid intake with increased thirst sensation [37] (associated with an activated renin-angiotensin-aldosterone system and vasopressin release) during and after exercise or dehydration are suggested as mechanisms of training-induced increases in extracellular fluid volume [38].…”
Section: Effects Of Exercise Training On Thermoregulation In Warm Andmentioning
confidence: 99%
See 1 more Smart Citation